REFRIGERATION MACHINES IN THE SYSTEM OF CONSISTENT MANAGEMENT OF ELECTRIC ENERGY CONSUMPTION OF THE COMPLEX ENTERPRISE-INDUSTRIAL REFRIGERATOR - KHOROLSKY, Valentyn; KORENETS, Yurii; OMELCHENKO, Oleksandr; HONCHARENKO, Volodymyr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The strategy of the coordinated management of electric consumption of the industrial refrigerator of the enterprise of a food complex on production of foodstuff is offered. The structure of the integrated intelligent power management system of the refrigerator enterprise has been developed, in which the systems of automated control of electricity metering and control of the refrigeration trajectory of refrigeration chambers are built-in. The system uses a situation center, industrial Internet of Things (IIoT), digital platform "FOOD" with software (freezing of food products). According to the ASUE-ACS command, the upper level of the industrial refrigerator and its software fulfill the set parameters of the portfolio of orders for active and reactive capacities of the food complex enterprises. An algorithm for controlling an industrial refrigerator during periods of power system power limitations has been developed. It is proved that the reduction of specific energy consumption for the production of one ton of frozen food during the period of power system power limitations and fan outages is possible only by optimizing the technological and energy parameters of refrigeration machines. Technologies for reducing energy consumption by controlling the reactive and active power of synchronous motors of reciprocating compressors and frequency control of asynchronous motors of screw compressors and asynchronous motors of evaporating condensers are presented. Simulation of the geometry of the in-chamber loading of the refrigerating chambers of an industrial refrigerator is performed. New approaches to the choice of adaptive regulators of synchronous motor exciters have been developed, which are coordinated in real time with the energy modes of operation of refrigeration machines and the geometry of refrigeration chamber loading. The possibility of improving the efficiency of power management regimes of food industry enterprises through coordinated automated control of cooling and freezing of meat products, poultry, fish, dairy products, fruits and the use of automated power management systems by building expert and human-machine decision making systems. The developed systems will allow to meet the requirements of energy generating companies for active and reactive loads, reduce costs in the power grid and maintain the voltage in the nodes of electrical receivers within the established norms.